Determinants of Smoking Behavior in Physical Education, Sports, and Health Teachers in Surakarta City in 2021 - Isnaini, Alfianita; Widjanarko, Bagoes; Indraswari, Ratih (Smart Medical Journal, 2024)
Background: Smoking is an unhealthy habit but is often encountered in everyday life. Teacher of Physical Education, Sports, and Health as one of the sports actors if active smoking can impair their physical fitness. Teachers contribute to instilling health values in students and making them role models. Teachers who smoke will give students the perception that smoking behavior is a common and harmless action that is feared to affect students who are still in the period of self-discovery, unstable, and easily influenced in smoking behavior. This study aims to determine what factors influence smoking behavior in Physical Education, Sports, and Health teachers in Surakarta City.Methods: This study was quantitative research with a cross-sectional approach and the sample was 81 Physical Education, Sports, and Health teachers using a proportionate stratified random sampling technique. The analysis of this study used univariate and bivariate analysis with the Chi-Square test.Results: The results showed 30.9% of respondents are active smokers, and 69.1% are non-active smokers. Variables related to smoking behavior are knowledge (p=0.000), the role of the respondent as a teacher (p=0.000), perceived seriousness (p=0.000), perceived benefits (p=0.017), attitude (p=0.000), subjective norms (p=0.000), and perceived behavioral control p=0.003).Conclusion: Knowledge, attitude, role as a teacher, perceived seriousness, perceived benefits, perceived behavioral control, and subjective norm have a relationship with smoking behavior, while age, income, cues to action, and perceived susceptibility are not related to smoking behavior.